HCM 2010 : highway capacity manual. (Transportation Research Board, 2010)
"HCM2010, which updates HCM2000, will significantly enhance how engineers and planners assess the traffic and environmental effects of highway projects by: providing an integrated multimodal approach to the analysis and evaluation of urban streets from the points of view of automobile drivers, transit passengers, bicyclists, and pedestrians; addressing the proper application of micro-simulation analysis and the evaluation of those results; examining active traffic management in relation to both demand and capacity; and exploring specific tools and generalized service volume tables, to assist planners in quickly sizing future facilities"--Transportation Research Board website.
Volumes 1-3 loose-leaf for updating.
"Volume 4 is an electronic-only volume that registered HCM users will be able to access over the Internet. This volume includes four types of content: supplemental chapters on methodological details and emerging issues; interpretations, clarifications, and corrections; comprehensive case studies; and a technical reference library. HCM 2010 is produced in U.S. customary units only. There is no CD-ROM or other electronic version of the contents of Volumes 1 through 3"--Transportation Research Board website.
Keywords: Highway capacity -- Handbooks, manuals, etc.; Traffic flow -- Handbooks, manuals, etc.; Traffic engineering -- Handbooks, manuals, etc.; Traffic estimation -- Handbooks, manuals, etc.; Highway planning -- Handbooks, manuals, etc.; Highway engineering -- Handbooks, manuals, etc.; Roads -- Design and construction -- Evaluation -- Handbooks, manuals, etc.; Urban transportation -- Planning -- Handbooks, manuals, etc.; City traffic -- Evaluation -- Handbooks, manuals, etc.; Streets -- Design and construction -- Evaluation -- Handbooks, manuals, etc.; elektronické knihy; electronic books